PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TABUNGANKU TERHADAP KEPUASAN NASABAH PADA PT. BANK SULSELBAR KANTOR CABANG BELOPA - Rosnaini Daga (AkMen JURNAL ILMIAH, 2019)
This study aims to analyze the effect of service quality and quality product on Saving product on customer satisfaction in PT. Bank Sulselbar Belopa Branch Office. The data analysis method used multiple linear regression and using SPSS version 24. The results showed that service quality has a positive and significant effect on customer satisfaction because it is worth 0.273 and is significant at 0.002. The quality of the Tabunganku product has a positive and significant effect because it is worth 0.309 and is significant at 0.004.